Black hole - Burns, Charles 1955- (Fantagraphics Books, 2017)
A chilling graphic novel set in suburban Seattle during the mid-1970s describes the lives of the area's teenagers, who are suddenly faced with a devastating, disfiguring, and incurable plague that has descended on the young people of Seattle
Originally issued in a twelve-issue comic book limited series, published first by Kitchen Sinks Press, then Fantagraphics. Published in collected form first by Pantheon Books, 2005
Keywords: Teenagers / Comic books, strips, etc; Plague / Comic books, strips, etc; Seattle (Wash.) / Comic books, strips, etc; Nineteen seventies / Comic books, strips, etc; Plague; Teenagers; Washington (State) / Seattle; Comic books, strips, etc; Comics (Graphic works); Graphic novels; Comic